Low toxic effects of a whitening strip to cultured pup cells - Soares, Diana Gabriela de Souza [UNESP]; Pontes, Elaine Cristina Voltolini [UNESP]; Ribeiro, Ana Paula Dias; Basso, Fernanda Gonçalves [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (My University, 2013)
To assess the trans-enamel and trans-dentin toxicity of a 10% hydrogen peroxide (HP) whitening strip to odontoblast-like cells (MDPC-23). Methods: Enamel surfaces of enamel/dentin discs adapted to artificial pulp chambers were subjected to two 30-minute whitening strip applications to obtain indirect extracts (DMEM + bleaching components that diffused across enamel and dentin). The extracts were applied for 1 hour to the cells for 1 or 5 days. A bleaching gel with 35% HP was used as the positive control. Cell viability (MTT assay) and morphology (SEM) as well as the quantity of HP in the extracts were assessed. Results: Discrete cell viability reduction (21.9%) associated with slight alterations in cell morphology occurred after application of the extracts for 5 days to the MDPC-23 cells (Tukey's test; P< 0.05). Lower enamel/dentin diffusion of HP was observed after the use of the whitening strip compared with the bleaching gel (Mann-Whitney; P< 0.05).
Keywords: Randomized clinical-trial; Bleaching gel; In-vitro; Peroxide penetration; Carbamide peroxide; Hydrogen-peroxide; Mdpc-23 cells; Efficacy; Office; Products